Troubled Helix – Tinjauan Multiperspektif Genetika dalam Bioetika - Dito Anurogo; Arli Aditya Parikesit (Cermin Dunia Kedokteran, 2021)
Dalam review ini, dibahas tinjauan multiperspektif genetika dalam bioetika. Dikemukakan prinsip-prinsip etika mutakhir, seperti: reciprocity, mutuality, solidarity, citizenry, dan universality. Dibahas pula prinsip-prinsip etika dan pemeriksaan genetika, seperti: otonomi, privasi, kebaikan, nonmaleficence, keadilan. Didiskusikan pula perspektif etnokultural dalam layanan genetika, milestones guideline etika dan regulasi riset biomedis internasional, prinsip-prinsip etika menurut Universal Declaration on Bioethics and Human Rights 2005, hak asasi manusia dan etika profesional: apresiasi translasional, perspektif utilitarianisme, perspektif deontologi, “simalakama” pemeriksaan genetika, globalisasi bioetika, etika bioinformatika, dan riset eugenik.In this review, a multiperspective review of genetics in bioethics is discussed. The latest ethical principles are mentioned, such as: reciprocity, mutuality, solidarity, citizenry, and universality. The principles of ethics and genetic inquiry, such as: autonomy, privacy, kindness, nonmaleficence, justice was also discussed. Also discussed are multiperspective, ethnocultural perspectives in genetic services, milestones of ethical guidelines and international biomedical research regulations, ethical principles according to the Universal Declaration on Bioethics and Human Rights 2005, human rights and professional ethics: translational appreciation, utilitarianism perspective, deontological perspective, the “simulacra” of genetic examination, bioethics globalization, bioinformatics ethics, and eugenic research.